Persistence and Subtype Stability of ADHD Among Substance Use Disorder Treatment Seekers. Issue 12 (October 2019) - Kaye, Sharlene; Ramos-Quiroga, Josep Antoni; van de Glind, Geurt; Levin, Frances R.; Faraone, Stephen V.; Allsop, Steve; Degenhardt, Louisa; Moggi, Franz; Barta, Csaba; Konstenius, Maija; Franck, Johan; Skutle, Arvid; et al.
Objective: To examine ADHD symptom persistence and subtype stability among substance use disorder (SUD) treatment seekers.Method: In all, 1, 276 adult SUD treatment seekers were assessed for childhood and adult ADHD using Conners' Adult ADHD Diagnostic Interview for Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ; CAADID). A total of 290 (22.7%) participants met CAADID criteria for childhood ADHD and comprise the current study sample.Results: Childhood ADHD persisted into adulthood in 72.8% ( n = 211) of cases. ADHD persistence was significantly associated with a family history of ADHD, and the presence of conduct disorder and antisocial personality disorder. The combined subtype was the most stable into adulthood (78.6%) and this stability was significantly associated with conduct disorder and past treatment of ADHD.Conclusion: ADHD is highly prevalent and persistent among SUD treatment seekers and is associated with the more severe phenotype that is also less likely to remit. Routine screening and follow-up assessment for ADHD is indicated to enhance treatment management and outcomes.